Assessment of skin barrier function in podoconiosis: measurement of stratum corneum hydration and transepidermal water loss. (28th February 2013) - Ferguson, J.S.; Yeshanehe, W.; Matts, P.; Davey, G.; Mortimer, P.; Fuller, C.
Summary Background Podoconiosis is a common cause of lymphoedema in barefoot workers in Ethiopia and other countries. It has severe consequences for patients' physical function, quality of life and economic status. Aims To investigate stratum corneum (SC) hydration and transepidermal water loss (TEWL) in patients with podoconiosis compared with controls. Methods In total, 55 patients and 20 controls were recruited. For each study subject, SC and TEWL measurements were taken, along with foot and lower leg circumferences. Measurements were compared between the patient and control groups. Results Foot circumferences tended to be higher in patients with podoconiosis, with the mean foot:leg circumference ratio being 1·19 (95% confidence interval 1·11–1·28) times that for controls (P = 0·001). There was no detectable difference between patients and controls in TEWL values (P > 0·05); however, SC hydration was significantly lower in patients vs. controls for the foot (P = 0·004) and lower leg (P = 0·046) sites. Conclusions Patients with podoconiosis have significantly lower SC hydration in the skin of their lower legs and feet than controls, which may lead to cracking and splitting, and increased risk of lymphoedema and infection.